The Modern Legislative Veto : Macropolitical Conflict and the Legacy of Chadha - Berry, Michael J. (Book collections on Project MUSE., 2016)
In The Modern Legislative Veto, Michael J. Berry uses a multi-method research design, incorporating quantitative and qualitative analyses, to examine the ways that Congress has used the legislative veto over the past 80 years. This parliamentary maneuver, which delegates power to the executive but grants the legislature a measure of control over the implementation of the law, raises troubling questions about the fundamental principle of separation of governmental powers.